2015
DOI: 10.1186/s12886-015-0155-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between a vascular endothelial growth factor gene polymorphism (rs2146323) and diabetic retinopathy: a meta-analysis

Abstract: BackgroundVascular endothelial growth factor (VEGF) is thought to play an important role in the pathogenesis of diabetic retinopathy (DR). Previous studies have associated the VEGF rs2146323 polymorphism with the risk of DR. However, the results of these studies are inconsistent. A meta-analysis was performed to evaluate the association between the VEGF rs2146323 polymorphism and the risk of DR.MethodsThe PubMed, EMBASE, Web of Science and Google Scholar literature databases until March 2015 were searched. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, another VEGF SNP, namely rs2146323 (C > A), is located in exon 3, rather than the predicted transcription factor binding sites. A recent meta‐analysis implied that there was a significant association between the rs2146323 (C > A) polymorphism and the risk of DR . Thus, the present study could complement these previous findings.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, another VEGF SNP, namely rs2146323 (C > A), is located in exon 3, rather than the predicted transcription factor binding sites. A recent meta‐analysis implied that there was a significant association between the rs2146323 (C > A) polymorphism and the risk of DR . Thus, the present study could complement these previous findings.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, it is possible that the influence of polymorphism -634C/G of the VEGF gene on DR is relatively small and dependent on the ethnicity and Our results suggest that polymorphism − 460 C/T, in the promoter region of the VEGF gene, is correlated with the risk of developing NPDR, but not PDR. In China, Wang, Jin, and Zhang (2008) and Zheng (2007) have investigated genotypes at the VEGF-460C/T locus and discovered that polymorphism correlated with the development of DR, with the C allele indicating susceptibility to DR. In contrast to our findings, studies of individuals in the UK (Ray et al, 2004) and India (Paine et al, 2012) have concluded that polymorphism − 460C/T of the VEGF gene represents an independent risk factor for PDR, while Awata et al (2002) found no influence of this polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta‐analyses have been conducted in order to confirm significant associations. VEGFA polymorphisms analysed include −634G > C(rs2010963), +5092C/A (rs2146323), −2578C/A (rs699947), −460T/C (rs833061), +936C/T (rs3025039) and −1154G/A (rs1570360) …”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%